2024
DOI: 10.3389/fpls.2023.1322986
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory function of the endogenous hormone in the germination process of quinoa seeds

Fang Zeng,
Chunmei Zheng,
Wenxuan Ge
et al.

Abstract: The economic and health significance of quinoa is steadily growing on a global scale. Nevertheless, the primary obstacle to achieving high yields in quinoa cultivation is pre-harvest sprouting (PHS), which is intricately linked to seed dormancy. However, there exists a dearth of research concerning the regulatory mechanisms governing PHS. The regulation of seed germination by various plant hormones has been extensively studied. Consequently, understanding the mechanisms underlying the role of endogenous hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…GAs play an important role in embryo growth and seed development and germination [35]. The application of exogenous GA 3 can modify the hormone balance in plant seeds and reduce the production of inhibitory substances.…”
Section: Discussionmentioning
confidence: 99%
“…GAs play an important role in embryo growth and seed development and germination [35]. The application of exogenous GA 3 can modify the hormone balance in plant seeds and reduce the production of inhibitory substances.…”
Section: Discussionmentioning
confidence: 99%
“…They found that commercial quinoa varieties range from no dormancy to strong dormancy, and seed coat thickness and eccentricity are particularly important traits affecting seed dormancy levels. Additionall, Zeng et al., (2024) characterised the dynamic profiles of eight endogenous hormones during quinoa seed germination using the HPLC-ESI-MS/MS and ELISA method, complemented with transcriptome network analyses using RNA-seq. They found that quinoa shared some common metabolic patterns with other crops during seed germination, but also exhibited a few quinoa-specific hormone changes that will require further attention.…”
mentioning
confidence: 99%
“…2) Improved analytical approaches and genomic resources have assisted new research in this area, such as the optimised hormone detection method used by Nelson et al. , the transcriptome sequencing by Zeng et al., 2024 and Nelson et al. , and the genetic map and genome assembly for mungbean used by Laosatit et al.…”
mentioning
confidence: 99%